Collective dynamics in single-particle motion for pure fluids - Bryk, T.M.; Mryglod, I.M.; Trokhymchuk, A.D. (Condensed Matter Physics, 2003)
Single-particle time correlation function Fs(k,t) of pure fluids is studied within the generalized mode approach. Analytical expression for self-intermediate scattering function, which contains oscillating terms, is obtained for three-variable basis set of single-particle dynamic variables. The meaning of oscillating contributions is discussed, and it is shown, that in lowdensity fluids the oscillating contributions do not appear. Our approach, developed within the five-variable scheme, is used for the analysis of MDderived single-particle time correlation function of Lennard-Jones fluid at two densities. It is shown, that the proposed scheme allows us to reproduce perfectly the function Fs(k,t) at the whole range of wavenumbers k studied. The generalized self-diffusion coefficient as a function of k is also calculated.